BRIDGING EMPLOYEE AGILITY AND FIRM PERFORMANCE: THE MEDIATING ROLE OF DYNAMIC CAPABILITY IN SME - Surya Nugraha; Anak Agung Ratih Wijayanti; Helena Ni Gusti Ayu Putu Pusparini; Ni Made Ernila Junipisa (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study examines the impact of employee agility on firm performance mediated by dynamic capability in SMEs in Bali. It aims to clarify how individual adaptability translates into improved organizational outcomes through dynamic capabilities encompassing sensing, seizing, and resource reconfiguration. Using a quantitative method, data from 122 SME managers were analyzed via structural equation modelling with partial least squares to test relationships among employee agility, dynamic capability, and firm performance. Results reveal that employee agility directly enhances firm performance and significantly fosters dynamic capabilities, which in turn positively affect performance and partially mediate the agility-performance link. This research bridges the gap between micro-level employee agility and macro-level dynamic capability, offering novel empirical evidence on their combined role in sustaining competitive advantage in SMEs. The findings underscore the importance for SME leaders and policymakers to develop agile employees alongside dynamic capabilities to succeed in uncertain, resource-limited markets. The study advances the dynamic capabilities framework by identifying employee agility as a critical micro-foundation driving organizational performance, providing strategic insights for SMEs targeting resilience and sustainable growth amid market volatility.